2003
DOI: 10.1007/s00464-003-8806-5
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy: why are general surgeons being excluded?

Abstract: General surgeons perform colonoscopies expeditiously, with as low a morbidity rate and as high a completion rate as their gastroenterology or colorectal surgery colleagues. As the results of this study confirm, general surgeons should not be excluded from endoscopy suites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 4 publications
1
23
0
1
Order By: Relevance
“…As principais complicações em polipectomia com alça diatérmica são sangramento, perfuração e dor abdominal 14,15 e estão associadas ao tamanho do pólipo 7,16,17,18,19,20 e são aqui demonstradas nas Tabelas 1, 2, 3 e 4. O tratamento destas complicações, em colonoscopia terapêutica, costuma ser por via endoscópica para hemorragia e conservador, não cirúrgico, para perfuração [21][22] .…”
Section: Discussionunclassified
“…As principais complicações em polipectomia com alça diatérmica são sangramento, perfuração e dor abdominal 14,15 e estão associadas ao tamanho do pólipo 7,16,17,18,19,20 e são aqui demonstradas nas Tabelas 1, 2, 3 e 4. O tratamento destas complicações, em colonoscopia terapêutica, costuma ser por via endoscópica para hemorragia e conservador, não cirúrgico, para perfuração [21][22] .…”
Section: Discussionunclassified
“…The authors emphasized the importance of designing endoscopy units in a way that both surgeons and gastroenterologists could work in a symbiotic environment, not as centers to be only used by gastroenterologists. In addition, distinctions are being made particularly in colonoscopy applications such as gastroenterologists and non-gastroenterologists in an attempt to create a perception that surgeons should not perform endoscopic procedures (26). However, in their colonoscopy series of 5237 cases, Mehran et al (26) showed that general surgeons were as successful as gastroenterologists and colorectal surgeons in terms of complication and cecal intubation rates.…”
Section: The Role Of Surgeons In Endoscopic Applicationsmentioning
confidence: 99%
“…In addition, distinctions are being made particularly in colonoscopy applications such as gastroenterologists and non-gastroenterologists in an attempt to create a perception that surgeons should not perform endoscopic procedures (26). However, in their colonoscopy series of 5237 cases, Mehran et al (26) showed that general surgeons were as successful as gastroenterologists and colorectal surgeons in terms of complication and cecal intubation rates. A study by Bielawska et al (27) showed that the risk of perforation during colonoscopy was twice as high with non-gastroenterologists than with gastroenterologists.…”
Section: The Role Of Surgeons In Endoscopic Applicationsmentioning
confidence: 99%
“…Some studies have shown that, compared to patients treated by general surgeons or other specialists, patients who underwent colonoscopy performed by a gastroenterologist were significantly more likely to have polyps detected [7][8][9] and removed 10 and had lower rates of bowel perforation, 11 and colorectal cancer was less likely to develop in these patients. 12 However, other studies have revealed no significant difference in polyp detection 13 or complication rates 14 between gastroenterologists and surgeons, with at least 1 study showing that gastroenterologists have significantly higher total complication rates than surgeons. 13 Despite these findings, little…”
mentioning
confidence: 98%